Degradation of Lignocellulose Biomass into Bio-oil and Biochar by Hydrothermal Liquefaction (HTL) - Lestari, Rizka; Maleiva, Lalak Tarbiyatun Nasyin; Yuliansyah, Ahmad T.; Hariyadi, Asful; Tarmidzi, Fadhil Muhammad (International Journal of Marine Engineering Innovation and Research, 2025)
Communities around the world are becoming more concerned about the environmental impact of using and heavily relying on fossil fuels, leading to a growing popularity of sustainable energy solutions. Biomass energy has become a popular topic of study around the world due to its sustainability. This study aims to investigate the feasibility of biomass waste valorization through its thermochemical or biochemical conversion into a sustainable, high-value energy commodity, thereby augmenting its economic and environmental value proposition. Hydrothermal liquefaction (HTL) was identified as the most effective method for treating biomass waste. Experiments were carried out by mixing water and biomass waste in a 500 mL autoclave batch reactor at temperatures ranging from 270 °C to 330 °C, with b/w ratios of 1:20, 2:20, and 3:20 and a retention time of 30 minutes. This study was additionally carried out under a starting pressure of 5 bar. Bio-oil had the highest product dispersion (84% at 330°C and a b/w ratio of 3:30). Meanwhile, the biochar yield was less than 10%. The solid product, on the other hand, had GCV values that were about the same as bituminous and sub-bituminous coals, at 6474 and 4888 cal/g, respectively. The carbon content of biochar at 270°C and 330°C is 50.86% and 66.77%, respectively, resulting from a variable b/w ratio of 2:20. GC-MS analyzed the highest-yielding product, bio-oil. The GC-MS study revealed a number of value-added chemicals resulting from the breakdown of hemicellulose, cellulose, and lignin compounds.